Liberia Public Expenditure Review Note : Meeting the Challenges of the UNMIL Security Transition - World Bank (World Bank, Washington, DC, 2013)
A history of poor governance culminated in nearly fifteen years (1989-2003) of brutal conflict that destroyed lives, key institutions and infrastructure, and brought the Liberian economy to a halt. The origins of the conflict were rooted in the marginalization and/or exclusion over many years of a large part of the Liberian population from political power and the economic wealth flowing from the country s substantial natural resources. The new government articulated a broad vision of a peaceful, secure, and prosperous Liberia as described in lift Liberia-the country s first poverty reduction strategy. During this period, Liberia made good progress as the economy recovered and growth was sustained, especially in the urban areas. This was supported by macroeconomic stability characterized by low inflation, essentially balanced budgets, and a significant reduction in external debt as well as significant inflows of foreign direct investment to the agriculture and mining sectors. A second democratic election took place in October 2011 with a run-off in November that led to victory for the incumbent party, a process that was conducted peacefully and benefited from United Nations Mission in Liberia (UNMIL) and broad international support. Liberia must overcome economic, institutional, and security hurdles. Recognizing the positive impacts of peace and security on Liberia, the World Bank in close collaboration with UNMIL is assisting the government to identify the core security functions and their associated costs as well as options to ensure a smooth security transition. As such, this report does not carry out an in-depth analysis of public expenditure in the security sector. Instead, the costing of the security is based on the draft transition plan prepared jointly by the government and UNMIL, alongside the relevant costs outlined in the Liberia peace building program, a central component of which is the development of regional justice and security hubs.